Surgical Treatment of Congenital Tail Fibrosarcoma in a Three-Year-Old Crossbred Jersey Cow - Madeena Begum, M; E.Kalaiselvan; S.Jayabharathi; M.Balagangatharathilagar; N.Krishnaveni (The Indian Veterinary Journal, 2026)
A three-year-old crossbred Jersey cow was presented with a history of a huge mass on the tail to the large animal surgery unit. The mass was reported to be present at the tail from the time of birth. The size of the mass increased as the animal aged. On physical examination, a football-sized ulcerated mass was noticed at the cranial edge of the middle one-third of the tail. On palpation, no pain was evinced, and the mass was firm in consistency. On clinical examination, all the vital parameters were found to be normal. FNAC revealed fibrosarcoma, and hence the case was tentatively diagnosed as fibrosarcoma. Surgery was scheduled after the routine pre-operative haemato-biochemical analysis. Caudectomy was performed under epidural analgesia, and the tumour mass was sent for histopathological analysis. Histopathology confirmed the case as fibrosarcoma. With postoperative antibiotics and supportive therapy, the animal recovered completely.